2008
DOI: 10.3171/foc.2008.25.10.e4
|View full text |Cite
|
Sign up to set email alerts
|

Acute clinical grading in pediatric severe traumatic brain injury and its association with subsequent intracranial pressure, cerebral perfusion pressure, and brain oxygenation

Abstract: Object The goal of this paper was to examine the relationship between methods of acute clinical assessment and measures of secondary cerebral insults in severe traumatic brain injury in children. Methods Patients who underwent intracranial pressure (ICP), cerebral perfusion pressure (CPP), and brain oxygenation (PbtO2) monitoring and who had an initial Glasgow Coma Scale score, Pedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…A much larger series in a different institution confirmed that cerebral hypoxia significantly increased risk of death and that implementation of a P bt O 2 -directed treatment protocol not only decreased mortality rate but improved 6-mo outcomes compared with historical controls, with greater improvements in outcome in the diffuse injury subgroup (161). Safety and utility of P bt O 2 monitoring in the pediatric population has also been demonstrated (162), as has the correlation with compromised values and outcome, and the occurrence of cerebral desaturations despite achieving other therapeutic targets, such as MAP, peripheral oxygen saturation, hemoglobin, ICP, and CPP levels (163,164). In contrast, an observational study (165) demonstrated greater utilization of resources, higher intensity of treatment, and no reduction in mortality, but limitations of the study included the following: 1) placement of the monitors was at the discretion of the neurosurgeon; 2) the P bt O 2 monitored group was younger and more severely injured; and 3) the discharge Functional Independence Measure was used as the outcomes measure.…”
Section: Brain Tissue Oxygenationmentioning
confidence: 93%
“…A much larger series in a different institution confirmed that cerebral hypoxia significantly increased risk of death and that implementation of a P bt O 2 -directed treatment protocol not only decreased mortality rate but improved 6-mo outcomes compared with historical controls, with greater improvements in outcome in the diffuse injury subgroup (161). Safety and utility of P bt O 2 monitoring in the pediatric population has also been demonstrated (162), as has the correlation with compromised values and outcome, and the occurrence of cerebral desaturations despite achieving other therapeutic targets, such as MAP, peripheral oxygen saturation, hemoglobin, ICP, and CPP levels (163,164). In contrast, an observational study (165) demonstrated greater utilization of resources, higher intensity of treatment, and no reduction in mortality, but limitations of the study included the following: 1) placement of the monitors was at the discretion of the neurosurgeon; 2) the P bt O 2 monitored group was younger and more severely injured; and 3) the discharge Functional Independence Measure was used as the outcomes measure.…”
Section: Brain Tissue Oxygenationmentioning
confidence: 93%
“…PTS also did not correlate with the elevation in ICP, as reported by Figaji et al However, the author found a correlation with the pediatric mortality rate of -2, which is a good parameter to be analyzed in future studies. 26 In the present study, patients were divided into groups with scores of three to five and six to eight in the GCS. There was no difference in the occurrence of ICH between the groups, unlike a previous study with pediatric patients with severe TBI, in which the presence of abnormal positions at the time of admission correlated with the occurrence of refractory ICH.…”
Section: Discussionmentioning
confidence: 99%
“…PbtO2 monitoring is almost exclusively used in combination with other cerebral non-invasive and invasive monitoring modalities, in particular intracranial pressure [ICP] monitoring [4, 6, 17, 22, 24, 26, 32, 33, 50, 51, 53, 55, 72, 81, 88 202, 91, 130, 176, 187, 203, 206, 219-223], cerebral perfusion pressure (CPP) monitoring [3,4,10,25,178,187,198,[224][225][226], jugular venous saturation (JvDO2) monitoring [184,190,206,227,228] 88 202, 178, 237], regional cerebral blood flow measurements (rCBF) [47,[240][241][242], near infrared spectroscopy (NIRS) [15,123,179,190,243], intracranial temperature measurements [9,97,99,141], oxygen-15 positron emission tomography (15O-PET) [230], continuous surface electroencephalogram [94], and cortical spreading depolarizations (CSD) monitoring using subdural electrocorticography (ECoG) strip electrodes [244].…”
Section: Clinical Applicationsmentioning
confidence: 99%